Hepatosplenic Protective Actions of Spirulina platensis and Matcha Green Tea Against Schistosoma mansoni Infection in Mice via Antioxidative and Anti-inflammatory Mechanisms - Ramez, Amany M.; Elmahallawy, Ehab Kotb; Elshopakey, Gehad E.; Saleh, Amira A.; Moustafa, Samar M.; Al-Brakati, Ashraf; Abdo, Walied; El-Shewehy, Dina M. M. (Frontiers in Veterinary Science, 2021)
Schistosomiasis, a major parasitic illness, has high morbidity and negative financial effects in subtropical and tropical countries, including Egypt. The present study investigated the therapeutic effects of Spirulina platensis (SP) and matcha green tea (MGT) in Schistosoma mansoni-infected mice combined with tracing their possible antioxidant and anti-inflammatory impacts and their protective potency. A total of 60 Swiss albino mice were randomly allocated into six groups (n = 10): control group (CNT, received normal saline); SP–MGT group (received oral SP (3 g/kg b.w./day) plus MGT (3 g/kg b.w./day)); S. mansoni group (infected with unisexual female S. mansoni cercariae, 100 ± 10/mouse, using the tail immersion method); SP-infected group (infected with S. mansoni and received oral SP); MGT-infected group (received oral MGT after S. mansoni infection); and SP–MGT-infected group (received combined treatment of SP and MGT after S. mansoni infection). Treatment with SP and MGT started 4 weeks after S. mansoni infection and ended 10 weeks after. SP and MGT treatment (SP-infected and MGT-infected groups) and the combined treatment (SP–MGT-infected group) minimized the hepatic damage induced by S. mansoni; circulating alanine aminotransferase and aspartate transaminase decreased, and total protein, albumin, and globulin serum levels increased. The serum level of malondialdehyde significantly declined, and catalase, glutathione peroxidase, superoxide dismutase, and total antioxidant capacity increased in SP-infected, MGT-infected, and SP–MGT-infected groups compared with the infected group. Co-administration of SP and MGT reduced serum cytokine levels (TNF-α, IFN-γ, and IL-13) and increased IL-10 levels after S. mansoni infection compared with the infected group. Moreover, treatment with SP and/or MGT decreased the number of granulomas in hepatic and splenic tissues compared with the infected group. Collectively, our results suggest that combined SP and MGT treatment is effective for S. mansoni infection. Liver and spleen tissue alterations were improved, the antioxidant systems were stimulated, and the inflammatory response was suppressed. Further research is recommended to investigate the mechanisms of the combined SP and MGT treatment effects in order to facilitate the development of novel therapies against this disease.